2001
DOI: 10.1046/j.1537-2995.2001.41091086.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective RBC phenotype matching in a stroke‐prevention trial in sickle cell anemia: a multicenter transfusion trial

Abstract: This is the first multicenter study to show that extended RBC phenotyping can be implemented nationwide. Compared to studies, the alloimmunization rate dropped from 3 percent to 0.5 percent per unit, and hemolytic transfusion reactions dropped by 90 percent. It is recommended that all transfused sickle cell anemia patients be antigen matched for E, C, and Kell. Patients should be closely monitored during transfusions to avoid preventable risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
243
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(260 citation statements)
references
References 41 publications
5
243
1
4
Order By: Relevance
“…However, the immunological processes that occur during various SCD complications make it difficult to ascertain why ACS and VOC may be associated with significantly higher alloimmunization rates than other acute SCD-related complications. Consistent with previous reports (Rosse et al, 1990;Tahhan et al, 1994;Vichinsky et al, 2001;Aygun et al, 2002;Castro et al, 2002;Sakhalkar et al, 2005;Lasalle-Williams et al, 2011), we also observed that unmatched (CEK) transfusion was associated with an increased risk of alloimmunization in both univariate and multivariate analysis. In fact we observed the same alloimmunization rate (2Á6%) in CEK matched transfusions as reported by Sakhalkar et al (2005), and detected no antibodies following level 3 or higher matching despite the fact that our transfusions were strictly administered to a SCD population defined as 'responders.'…”
Section: Discussionsupporting
confidence: 92%
“…However, the immunological processes that occur during various SCD complications make it difficult to ascertain why ACS and VOC may be associated with significantly higher alloimmunization rates than other acute SCD-related complications. Consistent with previous reports (Rosse et al, 1990;Tahhan et al, 1994;Vichinsky et al, 2001;Aygun et al, 2002;Castro et al, 2002;Sakhalkar et al, 2005;Lasalle-Williams et al, 2011), we also observed that unmatched (CEK) transfusion was associated with an increased risk of alloimmunization in both univariate and multivariate analysis. In fact we observed the same alloimmunization rate (2Á6%) in CEK matched transfusions as reported by Sakhalkar et al (2005), and detected no antibodies following level 3 or higher matching despite the fact that our transfusions were strictly administered to a SCD population defined as 'responders.'…”
Section: Discussionsupporting
confidence: 92%
“…Attempting to identify blood lacking the antigen to which an antibody is formed can be difficult [6,7]. Matching red blood cell components between donors and recipients for more than ABO and Rh blood groups may decrease the rate of alloimmunization and the number of hemolytic reactions among recipients [8]. Blood donors from a similar ethnic group may maximize the yield of blood donors that are phenotypically compatible.…”
Section: Introductionmentioning
confidence: 99%
“…The exact number of cumulative transfusions from birth to first antibody formation is often not reported and in many studies it is unclear if the transfusion history has been fully traced, including transfusions outside the reporting centers [9,10,12,[14][15][16]28]. Yet, the exposure to foreign RBC antigens is a prerequisite for alloimmunization and higher incidences of alloimmunization have been observed in patients with a higher number of transfusions [5,7,8,27,29].…”
mentioning
confidence: 99%